Evaluation of the effects of blue-enriched white light on cognitive performance, arousal, and overall appreciation of lighting - Gagné, Valérie; Turgeon, Rose; Jomphe, Valérie; Demers, Claude M. H.; Hébert, Marc (Frontiers in Public Health, 2024)
Introduction Light’s non-visual effects on the biological clock, cognitive performance, alertness, and mental health are getting more recognized. These are primarily driven by blue light, which triggers specific retinal cells containing melanopsin. Traditionally, research on light has relied on correlated color temperature (CCT) as a metric of its biological influence, given that bluer light corresponds to higher Kelvin values. However, CCT proves to be an inadequate proxy of light’s biological effects. A more precise metric is melanopic Equivalent Daylight Illuminance (mel-EDI), which aligns with melanopsin spectrum. Studies have reported positive cognitive impacts of blue-enriched white light. It’s unclear if the mixed results are due to different mel-EDI levels since this factor wasn’t assessed. Method Given recent recommendations from experts to aim for at least 250 mel-EDI exposure daily for cognitive benefits, our aim was to assess if a 50-minute exposure to LED light with 250 mel-EDI could enhance concentration and alertness, without affecting visual performance or comfort compared to conventional lighting producing around 150 mel-EDI. To ensure mel-EDI’s impact, photopic lux levels were kept constant across conditions. Conditions were counterbalanced, parameters included subjective sleepiness (KSS; Karolinska Sleepiness Scale), concentration (d2-R test), visual performance (FrACT; Freiburg Visual Acuity and Contrast Test), general appreciation (VAS; Visual Analogous Scale), preferences and comfort (modified OLS; Office Lighting Survey). Results The experimental light significantly reduced sleepiness (p = 0.03, Cohen’s d = 0.42) and also decreased contrast sensitivity (p = 0.01, Cohen’s d = 0.50). The conventional light was found to be more comfortable (p = 0.002, Cohen’s d = 0.62), cheerful (p = 0.02, Cohen’s d = 0.46) and pleasant (p = 0.005, Cohen’s d = 0.55) while the experimental light was perceived as brighter (p = 0.004, Cohen’s d = 0.58) and tended to be more stimulating (p = 0.10). Notably, there was a preference for conventional lighting (p = 0.004, Cohen’s d=0.56) and concentration was equally improved in both conditions. Discussion Despite the lack of further improvement in concentration from exposure to blue-enriched light, given the observed benefits in terms of vigilance, further research over an extended period would be justified. These findings could subsequently motivate cognitive optimization through lighting for workers that would benefit from artificial lighting such as in northern regions.